2016
DOI: 10.1080/02699931.2016.1170668
|View full text |Cite
|
Sign up to set email alerts
|

The effects of active worrying on working memory capacity

Abstract: According to the Attentional Control Theory of Anxiety (Eysenck, Derakshan, Santos & Calvo, 2007), worry, a crucial component of anxiety, impairs task performance outcome(s) through its direct effect on working memory capacity (WMC), by using up the limited resources available for performance thus reducing attentional control. We tested this hypothesis in the current study by examining the causal influence of active worrying on WMC in a sample of undergraduate university students assigned either to a worry con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…showing that repetitive thinking during distress interferes with adaptive problem solving (Ehring et al, 2011;Lyubomirsky, Kasri, & Zehm, 2003;Sari, Koster, & Derakshan, 2016). Following these arguments, the current findings could indicate that an increased attentional focus on the mother additionally depletes the capacity to self-regulate of children that think repetitively about their mother during distress.…”
Section: Running Head: Increased Focus On Mother and Depressive Symptomsmentioning
confidence: 54%
See 1 more Smart Citation
“…showing that repetitive thinking during distress interferes with adaptive problem solving (Ehring et al, 2011;Lyubomirsky, Kasri, & Zehm, 2003;Sari, Koster, & Derakshan, 2016). Following these arguments, the current findings could indicate that an increased attentional focus on the mother additionally depletes the capacity to self-regulate of children that think repetitively about their mother during distress.…”
Section: Running Head: Increased Focus On Mother and Depressive Symptomsmentioning
confidence: 54%
“…One possible explanation for this finding is that children with low RTm during distress and a more narrow attentional field around the mother more easily seek support during distress. Such an interpretation is in line with the observation that reduced repetitive thinking creates the cognitive capacity individuals need to rely on adaptive coping strategies (Ehring et al, 2011;Lyubomirsky et al, 2003;Sari et al, 2016).…”
Section: Running Head: Increased Focus On Mother and Depressive Symptomsmentioning
confidence: 58%
“…Nevertheless, another core problem of depressed patients is a significant reduction in working memory capacity (Onraedt & Koster, ). Future work should examine how rumination may cause this reduction in working memory capacity (Sari, Koster, & Derakshan, ). One potential mechanism may be that rumination prevents rehearsals of stimulus materials in spare moments during the task, a mechanism we have demonstrated to occur when we induced self‐referential processing in healthy participants (Daamen, van Vugt, & Taatgen, ; Taatgen et al., submitted).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this theoretical framework, an abundance of behavioral and neurological evidence indicates that anxiety reduces WM capacity for task-relevant information (Ashcraft & Kirk, 2001;Darke, 1988;Hayes, Hirsch, & Mathews, 2008;Leigh & Hirsch, 2011;Moran, 2016;Qi, Chen, et al, 2014;Sari, Koster, & Derakshan, 2017;Stout & Rokke, 2010;Yao, Chen, & Qian, 2018;Yoon, LeMoult, Hamedani, & McCabe, 2018). Although some have proposed that low WM loads are more likely to be disrupted by anxiety (i.e., Two-Component Model;Vytal, Cornwell, Arkin, & Grillon, 2012), others have found that high loads are more likely to be impacted by anxiety (Ashcraft & Kirk, 2001;Eysenck & Calvo, 1992;Eysenck et al, 2007;Lavric, Rippon, & Gray, 2003;Shackman et al, 2006).…”
mentioning
confidence: 89%
“…Although anxiety's disruptive effects on WM have been well demonstrated on WM tasks involving spatial and phonological modalities, the evidence regarding anxiety's effect on visual WM capacity is inconsistent (see Moran, 2016). Although previously mentioned work identified deficits in visual WM associated with anxiety (Qi, Chen, et al, 2014;Sari et al, 2017;Stout & Rokke, 2010;Yao et al, 2018), others have found that anxiety, specifically social anxiety, improved visual WM capacity (Moriya & Sugiura, 2012). However, it should be noted that Moriya and Sugiura's (2012) work included socially anxious university students in East Asia and that their findings may instead reflect an interaction between culture and type of anxiety.…”
mentioning
confidence: 99%